Antifungal potential of volatiles produced by Bacillus subtilis BS-01 against Alternaria solani in Solanum lycopersicum - Awan, Zoia Arshad; Shoaib, Amna; Schenk, Peer M.; Ahmad, Ajaz; Alansi, Saleh; Paray, Bilal Ahamad (Frontiers in Plant Science, 2023)
Bacterial biocontrol agent/s (BCAs) against plant diseases are eco-friendly and sustainable options for profitable agricultural crop production. Specific beneficial strains of Bacillus subtilis are effective in controlling many fungal diseases including Alternaria blight caused by a notorious pathogen “Alternaria solani”. In the present study, the biocontrol attributes of a newfangled strain of B. subtilis (BS-01) have been investigated and its bioactive compounds were also identified against A. solani. The volatile organic compounds (VOCs) produced by BS-01 in organic solvents viz., n-hexane, dichloromethane, and ethyl acetate were extracted and their antifungal efficacy has evaluated against A. solani. Also, the preventive and curative biocontrol method to reduce the fungal load of A. solani was estimated by both foliar and seed applications on infected tomato plants as determined by quantitative PCR assays. Results showed that antifungal bioassays with various concentrations (10-100 mg mL-1) of extracted metabolites produced by BS-01 in ethyl acetate fraction showed the highest inhibition in fungal biomass (extracellular metabolites: 69-98% and intracellular metabolites: 48-85%) followed by n-hexane (extracellular metabolites: 63-88% and intracellular metabolites: 35-62%) and dichloromethane (extracellular metabolites: 41-74% and intracellular metabolites: 42-70%), respectively. The extracted volatiles from BS-01 were identified via GC-MS analysis and were found in great proportions in the organic fractions as major potent antifungal constituents including triphenylphosphine oxide; pyrrolo[1,2-a] pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl); pyrrolo[1,2-a] pyrazine-1,4-dione, hexahydro-3-(phenylmethyl); n-hexadecanoic acid; n-tridecan-1-ol; octadecane; octadecanoic acid; eicosane and dodecyl acrylate. Growth chamber bioassay revealed that both foliar and seed application of BS-01 on tomato plants previously or subsequently infected by A. solani significantly reduced the pathogen load on inoculated tomato foliage. Separate or mixture of these bioactive VOCs had the potential to mitigate the tomato early blight disease severity in the field that would act as a sustainable plant protection strategy to generate profitable tomato production.